Nursing care of patients after laryngeal surgical procedures - Wamka, Malwina; Mackiewicz-Nartowicz, Hanna; Sinkiewicz, Anna (Pielęgniarstwo Chirurgiczne i Angiologiczne/Surgical and Vascular Nursing, 2018)
Larynx surgery is often associated with temporary or permanent impairment of respiratory, phonatory and protective functions. For this reason, it requires specific nursing care especially in the first days after surgery. The paper presents the scope of proceedings with patients after surgical operations of the larynx based on the analysis of the literature and the authors’ own experience.